Shape Recovery and Secondary-Shape Forming in Polyurethane-Shape Memory Polymer - HAYASHI, Syunichi; EJIRI, Yoshihiro; HOSHIO, Kazumasa; TOBUSHI, Hisaaki (Transactions of the Japan Society of Mechanical Engineers Series A, 2007)
In shape memory polymers, large strain can be fixed at low temperature and thereafter can be recovered at high temperature. If the shape memory polymer is held at high temperature for a long time, the secondary-shape forming with irrecoverable strain appears. The secondary-shape forming can be applied to a new simple method of fabricating shape-memory polymer elements. In the present paper, the influence of the strain-holding conditions on shape recovery and the secondary-shape forming in polyurethane-shape memory polymer is investigated by the tension test for film and the three-point bending test for sheet. The higher the shape-holding temperature and the longer the shape-holding time, the higher the rate of secondary-shape forming is. The equation to express the rate of secondary-shape forming is formulated.